FORMULASI SEDIAAN SIRUP EKSTRA ETANOL DAUN ILER (Coleus atropurpureus (L.) Benth) DAN UJI AKTIVITAS MUKOLITIK SECARA IN VITRO - Sulastri Herdaningsih; Dian Kartikasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Syrup is an oral liquid preparation containing sakarosa. The study aimed to test whether iler leaf extract (Coleus atropurpureus (L.) Benth) could be formulated as a syrup preparation then tested for physical properties and mucolytic activity. The experimental method used to test the mucolytic activity of iler leaf extract syrup in vitro is to measure the viscosity of duck egg whites added to the test solution every 15 minutes, namely at the 0th, 15th, 30th, 45th and 60th minutes. Testing of mucolytic activity was carried out on iler leaf extract syrup with concentrations of 3%, 4.5% and 6%, positive control of acetylcysteine 0.2% and negative control of aquades. The results showed that iler leaf extract syrup at concentrations of 3%, 4.5% and 6% can be formulated as syrup preparations and is able to significantly decrease the viscosity of duck egg whites compared to negative control.